Один із гобеленів Національного музею мистецтв імені Богдана та Варвари Ханенків - Ярема-Винар, Ольга (Київський національний університет імені Тараса Шевченка, 2024)
Представлено найцікавіший гобелен з Національного музею мистецтв імені Богдана та Варвари Ханенків, визначено його датування, автора картону, за яким він був витканий, та вірогідну майстерню виготовлення, показано місце цього твору серед рідкісних виробів ткацького мистецтва у європейській скарбниці.

The relevance of the research. The museum's tapestry from the Bohdan and Varvara Khanenko National Museum of Arts is listed in accession registers of the museum as “The Meeting of David.”. The collection of historical tapestries in the Khanenko Museum has been collected over a certain time and was replenished without an outlined plan. Nevertheless, an interesting collection of tapestries of different periods and different levels of value has been formed. This suggests that they reflect the main stages of the development of tapestry production in Western Europe. The Bohdan and Varvara Khanenko National Museum of Arts owns 11 historical tapestries. When Ukraine became interested in tapestries, their production in Flanders and France, the main centres of tapestry production, was already declining. Therefore, the auctions, from which most of the items in the Khanenko collection came, were ungrouped series of tapestries, mostly without accompanying documents, which now creates difficulties in their comprehensive research. Collecting the most complete information about each conservation unit is very relevant and extremely important, as it makes it possible to trace Ukraine's ties with Europe in the early twentieth century. Thus, the purpose of the work is to present the most interesting tapestry from the National Museum of Arts named after Bohdan and Varvara Khanenko, to determine its dating and origin, and to show the place of this work among the rare pieces in the European treasury of these works of weaving art. The collection of historical tapestries from the Bohdan and Varvara Khanenko Museum can be divided into two groups according to their subject matter and plot: the first group includes thematic tapestries with multi-figure compositions; the second group includes tapestries with landscape images, or as they are also called verdure, which means ‘greenery’ in French. The first group is the tapestry ‘The Meeting of David’, which was kept in the museum's funds and is the subject of this article adorns the collection. Familiarity with the collections of tapestries in European museums and the available literature on the subject allows us to state that the closest analogy to the tapestry “The Meeting of David” from the Kyiv Museum is the tapestry from the Royal Palace in Madrid. It is one of the nine tapestries of the Historia de Teseo series, namely Theseus defeating the bull Marathon, which, with only minor differences, repeats the canvas of “The Meeting of David." It is concluded that: - the tapestry “The Meeting of David” from the Bohdan and Varvara Khanenko National Museum of Arts reflects the life of Theseus, not David; - it was weaved from cardboard by Antoine Salaert in the late 1620s in the European Baroque style; - it is a Flemish tapestry created in the workshop of Jean Raes le Jeune. Hence, the article shows the place of this work among the rare pieces in the European treasury of these amazing works of weaving art, which is one of the proofs of the spread of European culture to Ukraine.
One of the Tapestries of the Bohdan and Varvara Khanenko National Museum of Arts
Keywords: гобелен; Національний музей мистецтв імені Богдана та Варвари Ханенків; Фландрія; Франція; реставрація текстилю; вердюра; галон; tapestry; the Bohdan and Varvara Khanenko National Museum of Arts; Flanders; France; restoration of textiles; verdure; gallon